Towards the Reconstruction and Reinterpretation of al-Kulliyyāt al-Khams: A Study of Maqāṣid in the Interdisciplinary Islamic Studies Master's Program at UIN Sunan Kalijaga - Moh. Mufid (UIN Sunan Kalijaga Yogyakarta, 2025)
This article aims to examine the research trends on Maqāṣid Sharī'ah topics within the Interdisciplinary Islamic Studies Master's Program at UIN Sunan Kalijaga Yogyakarta. This study is significant for developing Maqāsid Shariah studies in state Islamic universities. The research method employed is a literature study, utilizing data from student theses on the topic of Maqāsid Shariah to reveal trends in studies over a six-year period from 2018 to 2023. The results indicate that student theses tend to focus on the following topics: (1) studies of the thoughts of Maqāsid figures, (2) thematic fiqh studies from a Maqāsid perspective, (3) legal studies from a Maqāsid Shariah perspective, (4) public policy studies related to Maqāsid, and (5) Maqāsid approaches to interpreting Quranic verses. Their studies successfully initiated a new discourse in Maqāsid research within the Indonesian context through the development of: The hifz al-mithāq discourse regarding the disbandment of Hizbut Tahrir Indonesia; The hifz al-khuṣūṣiyah discourse concerning the issue of personal data protection in the Draft Law on Personal Data Protection; and The hifz al-mujtama' discourse within the discussion of Islamic legal dialogue in a pluralistic society in Kaloran. In conclusion, the Interdisciplinary Islamic Studies Master's Program develops Maqasid al-Shari'ah studies by reconstructing and reinterpreting al-Kulliyāt al-Khams, while actively incorporating the dynamic Islamic and Indonesian discourses. Artikel ini bertujuan untuk mengkaji tren penelitian bertopik Maqāsid Syariah pada Program Magister Interdiscipliner Islamic Studies UIN Sunan Kalijaga Yogyakarta. Kajian ini penting untuk mengembangkan kajian Maqāsid Syariah di Perguruan Tinggi Islam Negeri. Metode penelitian ini adalah penelitian literatur dengan data berupa tesis mahasiswa bertema maqasid syariah untuk mengungkap tren studi selama enam tahun 2018-2023. Hasil penelitian menunjukkan bahwa pertama, kecenderungan penelitian tesis mahasiswa terfokus pada topik penelitian berikut: (1) kajian pemikiran tokoh maqasid; (2) kajian fikih tematik dengan perspektif maqāsid; (3) kajian yuridis hukum dengan perspektif maqāsid syariah (4) kajian kebijakan publik terkait maqāsid dan (5) kajian maqāsid sebagai pendekatan penafsiran ayat-ayat al-Quran. Studi mereka berhasil melahirkan wacana baru dalam kajian maqāsid dalam konteks Indonesia melalui pengembangan wacana hifz al-mitsāq dalam konteks pembubaran Hitbut Tahrir di Indonesia, wacana hifz al-khusūsiyah pada isu perlindungan data pribadi dalam Rancangan Undang-Undang Perlindungan Data Pribadi dan wacana hifz al-mujtama' pada diskursus dialog hukum Islam dalam masyarakat majemuk di Kaloran. Dalam konteks ini, dapat disimpulkan bahwa studi maqasid syariah di Program Magister Interdiscipliner Islamic Studies mengembangkan studi maqasid melalui rekonstruksi dan reinterpretasi kulliyat al-khams dengan mempertimbangkan wacana keislaman dan keindonesiaan yang dinamis.